Quantification and method to select nucellar plants of Poncirus trifoliata - Oliveira, Roberto Pedroso de; Scivittaro, Walkyria Bueno; Radmann, Elizete Beatriz (Pesquisa Agropecuaria Brasileira, 2003)
The aim of this work was to quantify the percentage of zygotic and nucellar plants of Poncirus trifoliata (L.) Raf. in an open pollinated population, and to evaluate the efficiency of the morphology and vigor-based selection method of nucellar plants. Seeds from mature fruits were sowed in plastic tubes of 50 cm3. After 150 days the plants were transferred to plastic bags of 4,8 dm3. Leaf morphology and height of plants were evaluated 300 days after sowing. Genetic characterization was carried out by isoenzymatic systems. In average, 1.07 plants were obtained per seed and the maximum value was two plants per seed. In these cases, both plants were characterized as nucellar by isoenzymes, although showing different and smaller size than the average of the rest of the plants. Zygotic plants identified were 5.9% of the population and were distributed in the classes of smaller size, showing genetic depression. Plants showing hybrid vigor were not observed. The differentiation of nucellar from zygotic plants was not possible by leaf morphological characters. The visual elimination of the smaller plants, about 30% of the population, is an efficient method to select trifoliata nucellar plants produced in plastic tubes under protected environment.